Pathogenesis of muscle weakness in inflammatory myositis - Sai Kumar Dunga; T G Sundaram; Chengappa G Kavadichanda (Indian Journal of Rheumatology, 2020)
Idiopathic inflammatory myositis (IIM) is a heterogeneous group of autoimmune diseases. These are characterized by muscle weakness and fatigue along with other systemic manifestations, ranging from pulmonary alveolitis to vasculopathic ulcers. Muscle weakness is encountered in a majority of individuals with IIM. Several hypotheses for muscle weakness have been proposed, but none have been convincingly proven. Understanding of the pathophysiology of muscle weakness is necessary to better delineate therapeutic options and tailor exercise regimens in patients with IIM. In this review, we have attempted to delineate the immune and nonimmune pathways implicated in muscle weakness and integrated them with the clinical, histopathological, and imaging findings in IIM.